Experimental investigation of bedding plane orientation on the rockburst behavior of sandstone - He, M. C. (2013)
Rockburst is a violent rock failure process which poses a significant threat to human safety in mining and tunneling construction. Although many in situ investigations provided valuable insights on the rockburst mechanism, the failure and rock fragmentation process during a rockburst cannot be fully examined on the site. In this paper, a modified triaxial rock testing apparatus is employed to investigate the rockburst behavior of oriented sandstone. A high-speed camera is used to record the crack propagation and the ejection of rock fragments on the unloading surface. The microscopic characteristics of the fragments generated from the rockburst tests are observed using the scanning electron microscope (SEM) imaging technique. The trajectory sketches are drawn to calculate the initial velocities of the rock fragments ejected based on the photographs taken by the high-speed camera. The results show that the mass and velocity of fragments are the two main parameters for the identification of the energy-transferring process in the rockburst test. When the bedding orientation is perpendicular to the unloading surface, the rockburst is controlled by the specimen’s strength. However, when the bedding orientation is parallel to the unloading surface, the rockburst is dependent on the structural stability of the specimen.